Dual Inhibition of Pirarubicin-Induced AKT and ERK Activations by Phenformin Sensitively Suppresses Bladder Cancer Growth - Peng, Mei; Deng, Jun; Zhou, Sichun; Xiao, Di; Long, Jiahui; Zhang, Nan; He, Caimei; Mo, Miao; Yang, Xiaoping (Frontiers in Pharmacology, 2019)
Activations of Akt or ERK pathway induced by clinical drugs promote therapeutic failure due to decrease of drug response and no available strategies have been developed to solve these problems. In this study, we found that pirarubicin (THP), one important chemotherapeutic drug for treating bladder cancer intravesically, dramatically elevated both phosphorylations of Akt and Erk1/2 in addition to inducing DNA damage. MK2206 or AZD6244, representative Akt and Erk1/2 inhibitors respectively, profoundly sensitized bladder cancer cells to THP treatment. Interestingly, we found that inhibition of single arm of either Akt or Erk1/2 pathway would induce the increase of another arm, indicating the existence of the crosstalk between these two pathways. Thus, simultaneous suppression of both signals may be needed for increasing the sensitivity of THP. In other hand, we revealed that phenformin efficiently inhibited both Akt and Erk1/2 phosphorylation in a dose dependent manner. Furthermore, we demonstrated that phenformin, mimicking dual inhibitors, plays dramatically synergistic action with THP both in vitro and in vivo. Our findings suggest that combination therapy of THP with dual inhibitors may constitute a successful strategy for improving chemotherapy response.